The X-chromosome and susceptibility to ankylosing spondylitis. - Hoyle, E; Laval, S; Calin, A; Wordsworth, B; Brown, M (2000)
OBJECTIVE: Ankylosing spondylitis (AS) affects 0.25-1.0% of the population, and its etiology is incompletely understood. Susceptibility to this highly familial disease (lambda(s) = 58) is primarily genetically determined. There is a significant sex bias in AS, and there are differences in recurrence risk to the offspring of affected mothers and fathers, suggesting that there may be an X-linked recessive effect. We undertook an X-chromosome linkage study to determine any contribution of the X-chromosome to AS susceptibility. METHODS: A linkage study of the X-chromosome using 234 affected sibling pairs was performed to investigate this hypothesis. RESULTS: No linkage of the X-chromosome with susceptibility to AS was found. Model-free multipoint linkage analysis strongly excluded any significant genetic contribution (lambda > or = 1.5) to AS susceptibility encoded on the X-chromosome (logarithm of odds [LOD] <-2.0). Smaller genetic effects (lambda > or = 1.3) were also found to be unlikely (LOD <-1.0). CONCLUSION: The sex bias in AS is not explained by X-chromosome-encoded genetic effects. The disease model best explaining the sex bias in occurrence and transmission of AS is a polygenic model with a higher susceptibility threshold in females.